Sensus maxime cognitivus. Sinestesie come critica della “Ragion spaziale” - Tanca, Marcello (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
“Think mobility rather than stability is a challenge that makes to the social sciences giddy”. Geography is one of these social sciences that both must think about the mobility of the globe and at the same time redefine itself because of the processes of spatial dematerialisation and fragmentation that characterize the contemporary world. Therefore it is necessary to overcome the contradiction between the thesis that argues that with globalization the space is insignificant and the thesis that argues that globalization produces an increasing spatial differentiation. This oscillation depends on the fact that the word “globalization” does not describe a state of affairs (the immobile Earth) but a whole of many processes (the Mobile Earth).